Growth performance of Chhotanagpuri sheep under field condition - Maroof Ahmad,; D K Singh, (Journal of Livestock Biodiversity, 2025)
Present study was undertaken on 242 Chhotanagpuri lambs in tribal areas of Deoghar District of Jharkhand. The body weights at different ages viz. birth weight (BWT), 3-month (3-WT), 6-month (6-WT), 9-month (9- WT) and 12-month (12-WT) were recorded for the study. The overall body weights of Chhotanagpuri lambs were 1.76± 0.06, 6.52 ± 0.14, 10.43±0.17, 13.44±0.20 and 16.44±0.18 kg at birth, 3, 6, 9 and 12-month of age, respectively. Lambs born during winter season were significantly heavier at birth than those born duringsummer and monsoon.Male lambs weighted significantly heavier than the female lambs at different stages of growth. Body weight of male lambs at birth, 3, 6, 9 and 12-months of age were 1.86±0.04, 7.02±0.12, 11.02±0.13, 14.16±0.24 and 17.64±0.23 kg respectively. The corresponding values for females were 1.65 ± 0.04, 6.01 ± 0.18, 9.83 ± 0.22, 12.72 ±0.18 and 15.24±0.12 kg. The variations in birth weight and weights at different stages of growth up to 12-month of age due to dam's weight at lambing were also significant. The average daily gain in body weights of Chhotanagpuri lambs were estimated as 52.88 ± 1.44, 43.44±1.10 and 33.38±1.21 g/day during 0-3, 3-6 and 6-12 month of age, respectively.